The many lives of carbon - Hessen, D. O. (Dag Olav), 1956- (Reaktion Books Ltd, 2017)
"In its pure form carbon can be the soft graphite in a pencil or an immensely hard diamond. It is the basic building block of most of the cells in our bodies. Carbon attracts, and one of the most crucial relationships it forms is with oxygen, producing carbon dioxide, the gas vital to life on earth. This is the story of a chemical element, C, its myriad properties and its life cycle. It is the story of a balance between photosynthesis and cell respiration, between building and burning, life and death. Dag Olav Hessen navigates us through an exploration of the existence of carbon in minerals and rocks, wood and rainforests, and of carbon's role in processes such as the greenhouse effect and the carbon cycles, on both small and large scales. He explores the burning issue of climate change: how will ecosystems respond to global change? How bad could things get? Will the world's ecosystems recover? And what are our moral obligations? Neither alarmist nor moralistic, Hessen takes the reader on a journey from the atom to our planet in informative, compelling prose."--Jacket.